Arbuscular mycorrhizal fungus changes alfalfa response to pathogen infection activated by pea aphid infestation - Wang, Yajie; Li, Yingde; Duan, Tingyu (Frontiers in Microbiology, 2023)
Arbuscular mycorrhizal (AM) fungi are important for the resistance of plants to insect infestation and diseases. However, the effect of AM fungal colonization of plants response to pathogen infection activated by pea aphid infestation is unknown. Pea aphid (Acyrthosiphon pisum) and the fungal pathogen Phoma medicaginis severely limit alfalfa production worldwide. This study established an alfalfa (Medicago sativa)–AM fungus (Rhizophagus intraradices)–pea aphid–P. medicaginis experimental system to clarify the effects of an AM fungus on the host plant response to insect infestation and subsequent fungal pathogen infection. Pea aphid increased the disease incidence of P. medicaginis by 24.94%. The AM fungus decreased the disease index by 22.37% and enhanced alfalfa growth by increasing the uptake of total nitrogen and total phosphorus. The aphid induced polyphenol oxidase activity of alfalfa, and the AM fungus enhanced plant-defense enzyme activity against aphid infestation and subsequent P. medicaginis infection. In addition, the AM fungus increased the contents of jasmonic acid and abscisic acid in plants exposed to aphid infestation or pathogen infection. Abscisic acid and genes associated with the gene ontology term “hormone binding” were upregulated in aphid-infested or pathogen-infected alfalfa. The results demonstrate that an AM fungus enhances plant defense and signaling components induced by aphid infestation, which may contribute to improved defense against subsequent pathogen infection.